Towards a comprehensive evaluation of decentralization: a multidimensional insight of OECD countries - Poniatowicz, Marzanna; Konopka, Paweł; Piekutowska, Agnieszka (Technological and Economic Development of Economy, 2024)
The present paper introduces a novel methodology for analyzing decentralization across three dimensions: political, administrative, and fiscal. Considering the challenges in determining the degree of decentralization, we have constructed synthetic measures for assessing political (MPD), administrative (MAD), and fiscal (MFD) decentralization employing the TOPSIS method (Technique for Order Preference by Similarity to an Ideal Solution). The use of this method allowed the creation of a linear rank of OECD countries. Furthermore, on the basis of constructed synthetic measures and utilizing the k-means clustering method, we also constructed a non-linear grouping of those countries. This approach enabled us to achieve the final objective of our research, the revelation of varied interrelationships among the different dimensions of decentralization in selected OECD countries. The combined application of the TOPSIS and the k-means methods enhances the methodology for analyzing decentralization by offering a multidimensional perspective. Given the potential repercussions of negative outcomes, such as overt or covert centralization, the findings of our study could turn out to be of significant relevance. First published online 10 July 2024